Soils inventory of the Alberta Oil Sands Environmental Research Program study area - Lindsay, J. D.; Turchenek, L. W. (1982)
A soil survey of the Alberta Oil Sands Environmental Research Program (AOSERP) study area was initiated in 1976 as part of the program objective to establish a data base for the area. The purpose of this report and accompanying soil maps is to provide data on the kinds, characteristics, location, and areal distribution of soils in the AOSERP study area. The soil maps indicate types of soils and landforms within delineated areas. The mapping approach used is similar to the ecological method of classification in which land areas are mapped rapidly and at a small or reconnaissance scale by means of air photo interpretation and supporting field checks on 1:50,000 airphotos. Recurring patterns of soils, landforms, and vegetation were delineated. The information was transferred first to 1:50,000 preliminary maps and then to eight 1:126,720 maps which accompany this report. General characteristics of vegetation are provided in this report, but more detailed information must be derived from AOSERP vegetation maps. In addition to airphoto interpretation, the information on soil maps is based on about four field checks per township and on analyses of samples from 130 soil profiles. The predominant upland soils in the study area are Gray Luvisols, developed on loamy to clayey, morainal and glaciolacustrine deposits; and Dystric Brunisols, developed on sandy glaciofluvial and eolian materials. Gleysolic soils occupy a significant proportion of the landscape in many areas. Gleysols and Regosols occur on recently deposited fluvial materials, which occur in stream channel, fan and apron, and delta landforms. Solonetzic soils are associated with Luvisols on some of the clayey glaciolacustrine plains. Soils of low-lying, poorly drained areas are mainly Organic. These soils, formed in and fen peats, occupy a considerable portion of the area, and vary from less than 1 m to several metres in thickness. Soil formed in peat and which have permafrost layers in them, the Organic Cryosols, are extensive in the Birch Mountains Upland and ...